Perempuan Minangkabau dalam Politik - Nurwani Idris (Humaniora, 2010)
The aim of this study is to investigate Minangkabau women in politics who are well known for their egalitarian characteristics and have a central position in their community. There is a great gap between women representation and equality. In general, women's political representation and position in local politics are still low in West Sumatera. In fact, there is no causal relationship between women's egalitarian characteristics and their position in politics. In other words, the egalitarian characteristics do not significantly influence votes they may have in general election, since share of votes may depend greatly on electoral processes, such as recruitment systems; relationship with voters and social network with social organizations; relevant regulations providing more opportunities and facilitating women in their efforts to accomplish the elected post. To succeed in politics, they must have high interests in politics and make optimal efforts in a progressive and sustainable way.